Transcript Profiling of MIKCc MADS-Box Genes Reveals Conserved and Novel Roles in Barley Inflorescence Development - Kuijer, Hendrik N. J.; Shirley, Neil J.; Khor, Shi F.; Shi, Jin; Schwerdt, Julian; Zhang, Dabing; Li, Gang; Burton, Rachel A. (Frontiers in Plant Science, 2021)
MADS-box genes have a wide range of functions in plant reproductive development and grain production. The ABCDE model of floral organ development shows that MADS-box genes are central players in these events in dicotyledonous plants but the applicability of this model remains largely unknown in many grass crops. Here we show that transcript analysis of all MIKCc MADS-box genes through barley (Hordeum vulgare L.) inflorescence development reveals co-expression groups that can be linked to developmental events. Thirty four MIKCc MADS-box genes were identified in the barley genome and single nucleotide polymorphism (SNP) scanning of 22,626 barley varieties revealed that the natural variation in the coding regions of these genes is low and the sequences have been extremely conserved during barley domestication. More detailed transcript analysis showed that MADS-box genes are generally expressed at key inflorescence developmental phases and across various floral organs in barley, as predicted by the ABCDE model. However, expression patterns of some MADS genes, for example HvMADS58 (AGAMOUS subfamily) and HvMADS34 (SEPALLATA subfamily), clearly deviate from predicted patterns. This places them outside the scope of the classical ABCDE model of floral development, and demonstrates that the central tenet of antagonism between A- and C-class gene expression in the ABC model of other plants does not occur in barley. Co-expression across three correlation sets showed that specifically-grouped members of the barley MIKCc MADS-box genes are likely to be involved in developmental events driving inflorescence meristem initiation, floral meristem identity and floral organ determination. Based on these observations, we propose a potential floral ABCDE working model in barley, where the classic model is generally upheld, but that also provides new insights into the role of MIKCc MADS-box genes in the developing barley inflorescence.